Does Trigonometric Substitution Works?

Algebra Level 5

b 2 + 2 a 2 a b + a 2 + 2 c 2 a c + c 2 + 2 b 2 b c \large \dfrac { \sqrt { b^{ 2 }+2{ a }^{ 2 } } }{ ab } +\dfrac { \sqrt { { a }^{ 2 }+2c^{ 2 } } }{ ac } +\dfrac { \sqrt { { c }^{ 2 }+2{ b }^{ 2 } } }{ bc }

Let a a , b b and c c be positive reals satisfying a b + b c + c a = a b c ab+bc+ca=abc .

If the minimum value of the expression above can be expressed as m \sqrt m , where m m is a positive integer , find m m .


The answer is 3.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

P C
Jun 7, 2016

Relevant wiki: Hölder's Inequality

Rewrite the expression 1 a 2 + 2 b 2 + 1 c 2 + 2 a 2 + 1 b 2 + 2 c 2 \sqrt{\frac{1}{a^2}+\frac{2}{b^2}}+\sqrt{\frac{1}{c^2}+\frac{2}{a^2}}+\sqrt{\frac{1}{b^2}+\frac{2}{c^2}} From the condition, we get 1 a + 1 b + 1 c = 1 \frac{1}{a}+\frac{1}{b}+\frac{1}{c}=1 . So applying Minkowski Inequality 1 a 2 + 2 b 2 + 1 c 2 + 2 a 2 + 1 b 2 + 2 c 2 3 ( 1 a + 1 b + 1 c ) 2 = 3 \sqrt{\frac{1}{a^2}+\frac{2}{b^2}}+\sqrt{\frac{1}{c^2}+\frac{2}{a^2}}+\sqrt{\frac{1}{b^2}+\frac{2}{c^2}}\geq\sqrt{3\bigg(\frac{1}{a}+\frac{1}{b}+\frac{1}{c}\bigg)^2}=\sqrt{3} So m = 3 m=3 and the equality holds when { b 2 2 a 2 = a 2 2 c 2 = c 2 2 b 2 1 a + 1 b + 1 c = 1 \begin{cases} \frac{b^2}{2a^2}=\frac{a^2}{2c^2}=\frac{c^2}{2b^2} \\ \frac{1}{a}+\frac{1}{b}+\frac{1}{c}=1\end{cases} or a = b = c = 3 a=b=c=3

i also simplified it first

anshul sharma - 5 years ago
Huân Lê Quang
Jun 7, 2016

Obviously, a b + b c + c a = a b c > 0 ab+bc+ca\quad =\quad abc\quad >\quad 0 We have:

S = b 2 + 2 a 2 a b + a 2 + 2 c 2 a c + c 2 + 2 b 2 b c = c b 2 + 2 a 2 + b a 2 + 2 c 2 + a c 2 + 2 b 2 a b c = b 2 c 2 + 2 a 2 c 2 + a 2 b 2 + 2 c 2 b 2 + c 2 a 2 + 2 b 2 a 2 a b c S\quad =\quad \frac { \sqrt { b^{ 2 }+2{ a }^{ 2 } } }{ ab } +\frac { \sqrt { { a }^{ 2 }+2c^{ 2 } } }{ ac } +\frac { \sqrt { { c }^{ 2 }+2{ b }^{ 2 } } }{ bc } \\ \\ =\quad \frac { c\sqrt { b^{ 2 }+2{ a }^{ 2 } } +b\sqrt { { a }^{ 2 }+2c^{ 2 } } +a\sqrt { { c }^{ 2 }+2{ b }^{ 2 } } }{ abc } \\ \\ =\quad \frac { \sqrt { { b }^{ 2 }{ c }^{ 2 }+2{ a }^{ 2 }{ c }^{ 2 } } +\sqrt { { a }^{ 2 }{ b }^{ 2 }+2{ c }^{ 2 }{ b }^{ 2 } } +\sqrt { { c }^{ 2 }{ a }^{ 2 }+2{ b }^{ 2 }{ a }^{ 2 } } }{ abc } .

Applying the AM-GM inequality yields:

2 ( b 2 c 2 + a 2 c 2 ) 4 a b c 2 a 2 c 2 + a 2 c 2 = 2 a 2 c 2 2 ( b 2 c 2 + 2 a 2 c 2 ) 2 a 2 c 2 + 4 a b c 2 3 ( b 2 c 2 + a 2 c 2 + a 2 c 2 ) b 2 c 2 + a 2 c 2 + a 2 c 2 + 2 a 2 c 2 + 2 a b c 2 + 2 a 2 c 2 + 2 a b c 2 = ( b c + 2 a c ) 2 b 2 c 2 + 2 a 2 c 2 1 3 ( b c + 2 a c ) 2 b 2 c 2 + 2 a 2 c 2 3 3 ( b c + 2 a c ) ( b e c a u s e b c + 2 a c > 0 ) S i m i l a r l y , a 2 b 2 + 2 c 2 b 2 3 3 ( a b + 2 b c ) c 2 a 2 + 2 b 2 a 2 3 3 ( 2 a b + a c ) A d d t h e t h r e e i n e q u a l i t i e s s i d e t o s i d e y i e l d s b 2 c 2 + 2 a 2 c 2 + a 2 b 2 + 2 c 2 b 2 + c 2 a 2 + 2 b 2 a 2 3 3 3 ( a b + b c + a c ) = 3 ( a b + b c + a c ) = 3 a b c S 3 a b c a b c = 3 ( a b c > 0 ) E q u a l i t y h a p p e n s w h e n a = b = c = 3 S o m = 3 { 2(b }^{ 2 }{ c^{ 2 }+{ a }^{ 2 }{ c }^{ 2 })\quad \ge \quad 4ab{ c }^{ 2 } }\\ \\ { a }^{ 2 }{ c }^{ 2 }+{ a }^{ 2 }{ c }^{ 2 }\quad =\quad 2{ a }^{ 2 }{ c }^{ 2 }\\ \\ \Rightarrow \quad 2({ b }^{ 2 }{ c }^{ 2 }+2{ a }^{ 2 }{ c }^{ 2 })\quad \ge \quad 2{ a }^{ 2 }{ c }^{ 2 }+4ab{ c }^{ 2 }\\ \Rightarrow \quad 3({ b }^{ 2 }{ c }^{ 2 }+{ a }^{ 2 }{ c }^{ 2 }+{ a }^{ 2 }{ c }^{ 2 })\quad \ge \quad { b }^{ 2 }{ c }^{ 2 }+{ a }^{ 2 }{ c }^{ 2 }+{ a }^{ 2 }{ c }^{ 2 }+2{ a }^{ 2 }{ c }^{ 2 }+2ab{ c }^{ 2 }+2{ a }^{ 2 }{ c }^{ 2 }+2ab{ c }^{ 2 }\quad =\quad (bc+2ac)^{ 2 }\\ \Rightarrow \quad { b }^{ 2 }{ c }^{ 2 }+{ 2a }^{ 2 }{ c }^{ 2 }\quad \ge \quad \frac { 1 }{ 3 } { (bc+2ac) }^{ 2 }\\ \Rightarrow \quad \sqrt { { b }^{ 2 }{ c }^{ 2 }+{ 2a }^{ 2 }{ c }^{ 2 } } \ge \quad \frac { \sqrt { 3 } }{ 3 } (bc+2ac)\quad \quad \quad \quad (because\quad bc+2ac\quad >\quad 0)\\ \\ Similarly,\quad \sqrt { { a }^{ 2 }{ b }^{ 2 }+2{ c }^{ 2 }{ b }^{ 2 } } \ge \quad \frac { \sqrt { 3 } }{ 3 } (ab+2bc)\\ \quad \qquad \qquad \quad \quad \sqrt { { c }^{ 2 }{ a }^{ 2 }+2{ b }^{ 2 }{ a }^{ 2 } } \ge \quad \frac { \sqrt { 3 } }{ 3 } (2ab+ac)\\ \\ Add\quad the\quad three\quad inequalities\quad side\quad to\quad side\quad yields\\ \\ \sqrt { { b }^{ 2 }{ c }^{ 2 }+{ 2a }^{ 2 }{ c }^{ 2 } } +\sqrt { { a }^{ 2 }{ b }^{ 2 }+2{ c }^{ 2 }{ b }^{ 2 } } +\sqrt { { c }^{ 2 }{ a }^{ 2 }+2{ b }^{ 2 }{ a }^{ 2 } } \ge \quad \frac { \sqrt { 3 } }{ 3 } 3(ab+bc+ac)\quad =\quad \sqrt { 3 } (ab+bc+ac)\quad =\quad \sqrt { 3 } abc\\ \Rightarrow \quad S\quad \ge \quad \frac { \sqrt { 3 } abc }{ abc } \quad =\quad \sqrt { 3 } \quad (abc>0)\\ \\ Equality\quad happens\quad when\quad a=b=c=3\\ So\quad m\quad =\quad 3

Moderator note:

Good approach.

  1. It helps to break up the inequality into "equal parts", IE treat b 2 c 2 + 2 a 2 c 2 = b 2 c 2 + a 2 c 2 + a 2 c 2 b^2c^2 + 2a^2c^2 = b^2c^2 + a^2c^2 + a^2c^2 .
  2. When proving an intermediate step, it helps to think about what we want that step to be, instead of just approaching it directly from the start. IE once we see that we want b 2 c 2 + 2 a 2 c 2 1 3 ( b c + 2 a c ) \sqrt{b^2c^2+2a^2c^2}\geq\frac{1}{\sqrt{3}}(bc+2ac) , we should see if there is a shorter / more obvious approach.

To shortens the process you can apply Cauchy-Schwarz for the square roots, like this for an example b 2 c 2 + 2 a 2 c 2 = b 2 c 2 + a 2 c 2 + a 2 c 2 1 3 ( b c + 2 a c ) 2 b 2 c 2 + 2 a 2 c 2 1 3 ( b c + 2 a c ) b^2c^2+2a^2c^2=b^2c^2+a^2c^2+a^2c^2\geq\frac{1}{3}(bc+2ac)^2\Rightarrow\sqrt{b^2c^2+2a^2c^2}\geq\frac{1}{\sqrt{3}}(bc+2ac)

P C - 5 years ago

Log in to reply

Thanks for your comment!!!

Huân Lê Quang - 5 years ago
Figel Ilham
Jun 8, 2016

Rewriting the expression into: 1 a 2 + 2 b 2 + 1 c 2 + 2 a 2 + 1 b 2 + 2 c 2 \sqrt{\frac{1}{a^2}+\frac{2}{b^2}}+\sqrt{\frac{1}{c^2}+\frac{2}{a^2}}+\sqrt{\frac{1}{b^2}+\frac{2}{c^2}} OR 1 a 2 + 1 b 2 + 1 b 2 + 1 c 2 + 1 a 2 + 1 a 2 + 1 b 2 + 1 c 2 + 1 c 2 \sqrt{\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{b^2}}+\sqrt{\frac{1}{c^2}+\frac{1}{a^2}+\frac{1}{a^2}}+\sqrt{\frac{1}{b^2}+\frac{1}{c^2}+\frac{1}{c^2}} Rewriting the condition to 1 a + 1 b + 1 c = 1 \frac{1}{a} +\frac{1}{b} +\frac{1}{c} =1 . According to Cauchy-Schwarz inequality, we may find that ( 1 a + 1 b + 1 b ) 2 3 ( 1 a 2 + 1 b 2 + 1 b 2 ) \bigg(\frac{1}{a} + \frac{1}{b} +\frac{1}{b}\bigg)^2 \leq 3\bigg(\frac{1}{a^2} + \frac{1}{b^2} + \frac{1}{b^2}\bigg) ( 1 c + 1 a + 1 a ) 2 3 ( 1 c 2 + 1 a 2 + 1 a 2 ) \bigg(\frac{1}{c} + \frac{1}{a} +\frac{1}{a}\bigg)^2 \leq 3\bigg(\frac{1}{c^2} + \frac{1}{a^2} + \frac{1}{a^2}\bigg) ( 1 b + 1 c + 1 c ) 2 3 ( 1 b 2 + 1 c 2 + 1 c 2 ) \bigg(\frac{1}{b} + \frac{1}{c} +\frac{1}{c}\bigg)^2 \leq 3\bigg(\frac{1}{b^2} + \frac{1}{c^2} + \frac{1}{c^2}\bigg) OR 1 a 2 + 1 b 2 + 1 b 2 1 3 ( 1 a + 1 b + 1 b ) \sqrt{\frac{1}{a^2} + \frac{1}{b^2} + \frac{1}{b^2}} \geq \frac{1}{\sqrt{3}} \bigg(\frac{1}{a}+\frac{1}{b}+\frac{1}{b}\bigg) 1 c 2 + 1 a 2 + 1 a 2 1 3 ( 1 c + 1 a + 1 a ) \sqrt{\frac{1}{c^2} + \frac{1}{a^2} + \frac{1}{a^2}} \geq \frac{1}{\sqrt{3}} \bigg(\frac{1}{c}+\frac{1}{a}+\frac{1}{a}\bigg) 1 b 2 + 1 c 2 + 1 c 2 1 3 ( 1 b + 1 c + 1 c ) \sqrt{\frac{1}{b^2} + \frac{1}{c^2} + \frac{1}{c^2}} \geq \frac{1}{\sqrt{3}} \bigg(\frac{1}{b}+\frac{1}{c}+\frac{1}{c}\bigg)

Applying these to the expression, we get: 1 a 2 + 1 b 2 + 1 b 2 + 1 c 2 + 1 a 2 + 1 a 2 + 1 b 2 + 1 c 2 + 1 c 2 1 3 ( 3 a + 3 b + 3 c ) = 3 ( 1 a + 1 b + 1 c ) = 3 \sqrt{\frac{1}{a^2}+\frac{1}{b^2}+\frac{1}{b^2}}+\sqrt{\frac{1}{c^2}+\frac{1}{a^2}+\frac{1}{a^2}}+\sqrt{\frac{1}{b^2}+\frac{1}{c^2}+\frac{1}{c^2}} \geq \frac{1}{\sqrt{3}} \bigg(\frac{3}{a} +\frac{3}{b} + \frac{3}{c} \bigg) = \sqrt{3} \bigg(\frac{1}{a} + \frac{1}{b} +\frac{1}{c} \bigg) = \sqrt{3} which m = 3 m=3

awasome better approach

anshul sharma - 5 years ago
Anshul Sharma
Jun 9, 2016

why to do such a large claculation of course that is a formal approach but there is a short trick to as it is mentions a,b,c are the positive real no just try to satisfy the relation 1 a \frac{1}{a} + 1 b \frac{1}{b} + 1 c \frac{1}{c} =1 you will find a=b=c=3

but you do learn the formal because it is more important than since it opens your mind to possiblitys

Moderator note:

You have merely found an instance of a , b , c a,b,c that satisfies the given condition. Why must the maximum/minimum occur at this single instance? There is no justification of the "short trick" here.

You should learn to do the "formal" approach, because it is the correct way.

Why can't we have a = b = 2 c a = b = 2c ? You need to prove that a = b = c a=b=c must hold true for the minimum to occur.

Pi Han Goh - 5 years ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...